Enhancing access to prostheses in sports: a call to action for the future of Paralympic athletes - Simpson, A. I. (British Journal of Sports Medicine, 2025)
The recent call by Paralympic champion Richard Whitehead for improved access to advanced prosthetics within the National Health Service (NHS) underscores a critical issue in sports and rehabilitation: the need for prostheses that not only restore basic function but also empower individuals to excel in athletic pursuits. This editorial explores the importance of prostheses in sport, the current challenges faced by aspiring athletes and the imperative to enhance access to cutting-edge prosthetic technology to foster the next generation of Paralympic champions.